Transnational caregiving - Horvath, Rozalia (Kansas State University, 2014)
In 2011, about 13 percent of the U.S. population, approximately 40 million people, were foreign born in the United States. Many of them participate in transnational caregiving, either as children supporting their parents in their country of origin or parents moving to the U.S. to help their children. This report examines research on transnational caregiving between immigrant adult children and their parents. Following the caregiving definitions of Finch (1989), the articles were reviewed and categorized as economic support, accommodation, personal care, practical support and childcare, and emotional and moral support. Changes in family norms and roles, and the caregiving responsibilities after immigration, are also presented. Keywords: transnational, caregiving, immigrant, elderly, economic support, accommodation, personal care, practical support and childcare, and emotional and moral support, living arrangement.
Keywords: Transnational; Caregiving; Immigrants; Elderly; Changes in caregiving responsibilities; Gerontology (0351); Sociology (0626)